Metacognitive Thinking by University Students and its Relationship with Some Variables - Mohammed, Mohammed S. (Humanities Journal of University of Zakho, 2017)
The importance of the research comes through the importance of learning the skills of Meta cognitive thinking as it contributes when it is used by university students for research investigation and training to solve the problems. The research aimed to recognize the level of metacognitive thinking of Duhok university student's band to recognize the differences in abstract concepts in the levels of the metacognitive thinking skills according to gender distinction (male/ female) and specialist (scientific/human). The research in limited with the morning classes of Duhok University student for the academic year 2015-2016.The study contained a sample of (200) students taken randomly (100) male and (100) female. According to the instrument of the research; the researcher adopted a scale of the metacognitive thinking skills which consisted of (42) items distributed on three domains; for each domain (14) items and for every item (3) substitutions. Honesty and constancy of the instrument was found out which was (0.84). The maximum degrees of the scale were (126) and the minimum were (42) degrees whereas the hypothetical scale was (84) degrees. The researcher used the t-test for one sample t-test for two independent samples to recognize the distinctive concepts between the research differences due to gender and specialty and Pearson correlation to calculate constancy. And the most prominent result of the research was; the students of Duhok University, they are distinguished in awareness that is related to the metacognitive thinking skills. And the students (male) of human sciences use the metacognitive thinking skills better than female students; meanwhile the female students in scientific application departments use the metacognitive thinking skills better than male students. Also, the study mentioned the need for more researches to discover the effected factors of students marks contrast.